Relazione e Silenzio: Apofatismo ed ontologia trinitaria in Gregorio di Nissa - Maspero, Giulio (Augustinianum, 2013)
This in-depth study of the apophatic dimension crafted by Gregory of Nissa is the translation on the epistemological level of a new ontology, developed in debates with Arianism, and intended to expand classical metaphysics on the meaning of relationship. In Neoplatonic philosophy silence protects the absolute nature of the First Principle leaving expressive mediation to degrees of intermediate ontologies. Through trinitarian revelation God is manifested as a communion of love within which the external Logos is identified with the divine essence itself, in a unity founded upon relationship and will. Beginning from this new trinitarian ontology, Gregory sees in contemplation and in adoration, made up of silence and word, the human response to a free creative act of divine love and thus cognitive instruments, paths of access to the personal relationship of union with the Beloved.